Neuroscience findings on brain maturation – arguments for the exclusive criminal liability of young people - Dünkel, Frieder; Geng , Bernd; Passow , Daniel; Sakalauskas , Gintautas (Kriminologijos studijos, 2020)
Taking together all the evidence on the aetiology, development and differential processes of delinquent behaviour from childhood to adulthood, we dispose of important new evidence from the neurosciences, which, compared to traditional criminological, developmental, psychological and sociological evidence, increases our capacity to explain the age-crime curve. In particular, the right-hand side of the curve, indicating desistance from crime in young adulthood between the ages of 18 and 25, can be based on new insights from neuroscientific research on brain maturation and the development of self-control mechanisms. As a result, new questions about judicial reactions and interventions must be raised. If an individual’s brain is fully matured only in the mid-twenties, general criminal law is possibly inappropriate, and a specific youth or young-adult criminal law reflecting the transitional processes and the diminished culpability of young-adult offenders should rather be applied. In many European jurisdictions, the scope of youth justice has been extended upwards to 18–20 year-old adults, in the Netherlands even up to 22 years of age, a political decision affecting criminality and based on new neuroscientific evidence.